Other Spanish Practices. Women Architects' Approaches to Feminist Theories - Álvarez Lombardero, Nuria (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Since the end of the 20th century, a major change in the Spanish architecture has been the increase in female architects graduating from different schools of architecture, as opposed to a recent predominantly male past. However, this circumstance has not translated into the professional field, where the traditional canons of the profession and masculinized work patterns still hinder the progress of these women architects in their careers. In response to this situation, since the year 2000 a series of professional practices in architecture and urbanism have emerged which, led mainly by female architects, have adopted a different approach to the profession in which they have been able to find a place and form in which to develop their professional career. This article analyses how there is a rapprochement of these other practices in their design criteria, work methodologies and structural organization with certain discourses defended by different third and fourth wave feminist theories. In this sense, the article explores how these theories have opened new ways of practicing the profession in Spain, which could initially be identified as feminist, and discusses its possible use to define under these other practices.
Keywords: Feminist Practices; Feminine practices; Women Architects; Co-creation; Cooperativism; Interdisciplinarism